Effect of Supine Posture on Airway Blood Flow and Pulmonary Function in Stable Heart Failure - Ceridon, Maile L. (2011)
BACKGROUND: The aim of this study was to determine the relationship between body position, pulmonary function (PF) and bronchial blood flow (Q(aw)) in a group of heart failure (HF) and control subjects. METHODS: Thirty-six subjects were studied: 24 stable, ambulatory HF patients (HF: LVEF=27±6%, age=65±9yr) and 12 age- and sex-matched controls (CTRL: LVEF=60±7%, age=62±8yr). Measures of Q̇(aw) (soluble gas method) and PF were collected upright and following 30 min in the supine position. RESULTS: Q̇(aw) was similar between groups and remained unchanged with body position. Declines in forced vital capacity (FVC) and forced expiratory volume in 1 second (FEV(1)) with the supine position were observed in both groups; declines in forced expiratory flow 25–75% (FEF(25–75)) and FEF 75% (FEF(75)) with the supine position were observed in the HF group only. Changes in Q̇(aw) were related to changes in PF only in the HF patient groups (ΔFVC, %predicted, r=−0.45, p<0.04, ΔFEV(1) r=−0.61, p<0.01, ΔFEV(1) %predicted, r=−0.45, p<0.04). CONCLUSION: These data demonstrate that relationships between postural changes in Q̇(aw) and PF exist only in the HF population and that the bronchial circulation may contribute to postural PF decline in HF.